2009
DOI: 10.4102/sajpsychiatry.v15i4.185
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Paralysis and psychopathology

Abstract: Studies have reported a wide range in the prevalence of ISP. [5][6][7] This variation may stem from cultural factors and genetic differences in the populations studied. 6 It may also be due to differences in the methodologies of the studies. It is said that about 30 -50% of healthy individuals experience at least one episode of ISP in their lifetime, 5 although lower prevalence rates have been reported. In one study 7 it was found that as few as 5.7 -6.7% of the sample had experienced at least one episode of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Little research has been done to date on the relationship between SP and other diseases. Mume and Ikem, 2009 showed that there are signi cant differences in the prevalence of SP between healthy and sick people. In their study, SP was reported by 28% of healthy people, 44% of orthopedic patients, and 56% of patients complaining of multiple somatic complaints [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Little research has been done to date on the relationship between SP and other diseases. Mume and Ikem, 2009 showed that there are signi cant differences in the prevalence of SP between healthy and sick people. In their study, SP was reported by 28% of healthy people, 44% of orthopedic patients, and 56% of patients complaining of multiple somatic complaints [37].…”
Section: Discussionmentioning
confidence: 99%
“…Mume and Ikem, 2009 showed that there are signi cant differences in the prevalence of SP between healthy and sick people. In their study, SP was reported by 28% of healthy people, 44% of orthopedic patients, and 56% of patients complaining of multiple somatic complaints [37]. In a study by Takeuchi et al, 2002, the group of subjects who experienced isolated SP exhibited poorer performance, more complaints of physical, mental, and neurotic symptoms, and increased subjective fatigue compared to subjects who never experienced SP [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mume and Ikem, 2009 showed that there are significant differences in the prevalence of SP between healthy and sick people. In their study, SP was reported by 28% of healthy people, 44% of orthopedic patients, and 56% of patients complaining of multiple somatic complaints [ 37 ]. In a study by Takeuchi et al, 2002, the group of subjects who experienced isolated SP exhibited poorer performance, more complaints of physical, mental, and neurotic symptoms, and increased subjective fatigue compared to subjects who never experienced SP [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that may influence the occurrence of SP also include a high body mass index (BMI) [ 8 ], the level of general health [ 21 , 36 , 37 ], arterial hypertension [ 36 ], and chronic pain [ 22 ].…”
Section: Introductionmentioning
confidence: 99%